Synthesis and characterization of crotyl intermediates in Rh-catalyzed hydroformylation of 1,3-butadiene - Schmidt, Sebastian; Baráth, Eszter; Prommnitz, Tanja; Rosendahl, Tobias; Rominger, Frank; Hofmann, Peter (Organometallics, 2014)
Crotyl rhodium complexes like (κ2-L)Rh(η3-crotyl) and (κ2-L)Rh(η3-crotyl)(CO) (L = chelating phosphorus ligand) are important intermediates in hydroformylation catalysis of butadiene and related reactions. They are assumed to be responsible for the specific reactivity patterns of conjugated dienes. We prepared and characterized by X-ray crystallography several of these complexes with novel chelating bisphosphite ligands. (κ2-L)Rh(η3-crotyl) complexes exhibit a square-planar geometry, while their CO adducts (κ2-L)Rh(η3-crotyl)(CO) are trigonal-bipyramidal with the bisphosphite ligand in ee-bonding mode. Typically, the η3-crotyl unit can be oriented in several diastereomeric ways, of which oftentimes two or more are present in solution and in the solid state.